Upaya Optimalisasi Pemasaran Secara Digital pada UMKM Hi-Five Detailing dan Coating Batam - Lady Lady; Golan Hasan; Winson Winson; Tyana Tyana; Febby Febby (Economics and Digital Business Review, 2023)
The research about "Digital Marketing Optimization Efforts for Hi-Five Detailing and Coating Batam" contains the writing of implementation results for MSMEs to optimize marketing strategies. Utilization of digital marketing strategies includes social media, communication media, and interest content that will be implement. Social media is the tool used for implementation because it can reach a wider audience effectively and efficiently. MSMEs can convey marketing messages and information to the target audience in increasing company profits. The research technique used in this research is qualitative methods by conducting interviews with business owners and customer representatives. Interviews were conducted to understand the conditions of the informants and their responses regarding UMKM Hi-Five Detailing and Coating Batam. The research will provide an understanding of the benefits of digital marketing in the digitalization era for a business to do marketing. The conclusion shows that the results of using digital marketing strategies have an impact on improving customer or customer relationships. Relationships with customers that are built can support business development in obtaining company profits.